Energy-Saving Seamless Insulation Systems for Frame Buildings Using Foamed Polyethylene - Bessonov I.V.; Ter-Zakaryan K.A.; Zhukov A.D.; Mednikova E.A. (Problems of the Regional Energetics)
The purpose of the work was to substantiate the possibility of using rolled foamed polyethylene with a sheet thickness of 50 mm or more as thermal insulation for low-rise frame buildings. This goal was achieved by conducting experimental studies to determine the physical, mechanical and operational properties of foamed polyethylene, assessing the material's resistance to climatic influences and a full-scale assessment of the thermophysical characteristics of the material and the state of structures at the facility. The most significant results are: the results of determining the operating temperature range taking into account mechanical loading and tendency to creep; the results of assessing the effect of the reflective layer; the results of determining the tensile strength of the material on the surface and on the welded joint; field test results. It has been established that products based on foamed polyethylene are resistant to both climatic influences and mechanical loading, the material in the temperature range from minus 60 ° C to + 60 ° C has high operational resistance. The effect of the reflective layer applied to the foamed polyethylene on the mechanical characteristics of the material is insignificant, but it contributes to an increase in the thermal resistance of the insulating shell. Strength characteristics ensure the integrity of the seamless insulation envelope. The significance of the results obtained lies in the substantiation of the technical feasibility and economic feasibility of developing system solutions for the integrated insulation of frame buildings with rolled polyethylene foam.